Key national clusters in regional policy - Jegorow, Dorota (Krajowe klastry kluczowe w polityce regionalnej, 2016)
Development policy defining trends of changes in Polish economy is the source of many solutions implemented from the top down into economic practice. It also happens around initiatives realized in the area of clusters. The confrontation of program documents and research reports with cluster theory does not give rise to a positive evaluation of this organizational formula in the Polish economic practice. The newly established institution of key national clusters has been integrated into the complex public-private system far from universally accepted theoretical concept of a cluster. The chosen method of selecting key clusters raises serious concerns as it leads to the unauthorized segregation of market operators/participants in the access to public funds
Biblioteka Regionalisty, 2016, Nr 16, s. 17-28
Keywords: European funds; cluster; key national cluster; regional policy; regional development; fundusze europejskie; klaster; krajowy klaster kluczowy; polityka regionalna; rozwój regionalny